Museum Buildings. Construction and Design Manual. - Hoffmann, Hans Wolfgang (DOM Publ., 2016)
The museum as a building type and architectural space bear a complex relationship to each other. Architecture competes with the exhibited objects on the one hand and gives way to them on the other, enabling the museum to develop as regards content. This manual guide has its point of departure between both poles and targets both designers and users. The aim of the publication is to facilitate communication in the planning process of a museum, whether this is during the conceptual stage, the competition, or the design and construction phase. In addition to an introduction on the architectural history of the museum, the authors examine the key planning parameters involved in the conception and design of a contemporary museum. Buildings and projects provide inspiration for individual design work.
Keywords: Bebauung; Museum; Gebäudetyp; Architektur; Baukonstruktion; Entwurf; Planungsprozess; Kommunikation; Nutzer; Planungshilfe; Beispielsammlung; Museumsbau